Pengaruh Kegiatan Bermain Warna dengan Finger Painting terhadap Kemampuan Fisik Motorik Halus Anak Kelompok BI - Umahayatul Umahayatul; Muhammad Akil Musi (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
This study aims to determine the effect of the experimental method with color play activities to improve the fine motor skills of children in group B1 Kindergarten Nurul Fadhilah Tompobalang, Sumba Opu District, Gowa Regency. The formulation of the problem studied in this study is how the effect of the experimental method with color play activities to improve the fine motor skills of children in group B1 Kindergarten Nurul Fadhilah Tompobalang, Sumba Opu District, Gowa Regency. Experiment with color play activities to improve the physical motor skills of children in group B1 Kindergarten Nurul Fadhilah Tompobalang, Sumba Opu District, Gowa Regency. The research approach used is a quantitative approach with a Quasi Experimental Design research type. The population in this study was group B1 in Nurul Fadhilah Tompobalang Kindergarten, Sumba Opu District, Gowa Regency. Sampling in this research is purposive sampling. The sample in this study were 12 children. A total of 6 children as the experimental group and 6 children as the control group. Data collection techniques used were descriptive statistical analysis and non-parametric statistical analysis. Based on the results of the study, it can be concluded that the fine motor skills of children who were treated with color play activities with the experimental method in the experimental class were better than the control class, this proves that the experimental method with color playing activities has a significant effect on increasing the fine motor skills of early childhood.